Effect of Internal Factors and External Factors on Learning Achievement Intermediate Financial Accounting Course I - Syamsul Huda (Integrated Journal of Business and Economics (IJBE), 2017)
The purpose of this study was to determine the effect of internal and external factors of students on the achievement of intermediate financial accounting courses 1 partially and simultaneously. This type of research is quantitative, while the data used in this study is primary data in the form of questionnaires and secondary data in the form of midterm semester exam on intermediate financial accounting 1 semester odd academic year 2016/2017. Hypothesis testing using multiple regression analysis. With the result of regression equation is Y = 36,461 + 1,685 X_1-1,362X_2 with significant value less than 0,05. Simultaneously has significance value 0.000 < 0,05 and value F_count = 28,057 with value F_table 3,23, so value F_count > F_table. Hypothesis accepted, then internal and external factors have an effect on to learning achievement with R Square 0,603 or 60,3% dependent variable influenced independent variable and the rest 39,7% influenced by other factors not included in regression equation in this research. From the result, it can be concluded that the internal factors of students have a significant positive effect on learning achievement of intermediate financial accounting 1 and the external factors of students have a significant negative effect on intermediate financial accounting 1. While simultaneously there is significant influence between internal factors of students and external factors of students on intermediate learning achievement financial accounting 1.